Variation in Reproduction and Body Condition of the Ringed Seal (Phoca hispida) in Western Prince Albert Sound, NT, Canada, as Assessed Through a Harvest-based Sampling Program - Harwood, Lois A.; Smith, Thomas G.; Melling, Humfrey (ARCTIC, 2000)
Between 1992 and 1998, 869 ringed seals taken in the subsistence harvest in western Prince Albert Sound were sampled by two Inuvialuit seal monitors from Holman, Northwest Territories. Considering the 1992-98 data along with data from 1971-78, we found that the mean body-mass index (BMI) values for females (>= 7 yr) were significantly lower in 1974 than in all other years examined. At the same time, ovulation rates fell from 100% in 1971 and 1972 to lows of 42.9% (1974) and 64.3% (1975), with a return to 93.8% in 1976. Mature females that had ovulated had significantly higher BMI values than those that had not ovulated. In eastern Amundsen Gulf, 1974 was the most severe ice year on recent record, with the latest date of clearing of the landfast ice (6 September), the earliest date of new ice formation (4 October), and the fewest number of open water days (28 days). There were no years between 1992 and 1998 that compared to 1974 in reduced ovulation rates, reduced body condition, or severity of ice conditions. Between 1992 and 1998, mean BMI values for adult females and males were lowest in 1994 and highest in 1998, and all annual mean BMI values were between the extremes of the 1970s. This variation in condition in the 1990s did not coincide with a reduction in ovulation rates of mature females, which remained high (93.5-100%) from 1992 to 1998. In 1998, the landfast ice cleared 43 days earlier than the average clearing date for the 1990-98 period, apparently interrupting the lactation period for seal pups located at the periphery of the core breeding habitat. The apparent effects on growth and condition of unweaned pups came at a time when marine food appeared to be abundant and available to all age classes of ringed seals. Entre 1992 et 1998, 869 phoques annelés pris dans le cadre de la récolte de subsistance de l'ouest de la baie Prince-Albert ont fait l'objet d'échantillonnages par deux moniteurs inuvialuits de Holman (T. N.-O.), chargés de la surveillance des phoques. En tenant compte des données de ...